Analysis of Decision Making Using the Composite Performance Index Method in Improving Product Handling at UMKM Warung Nasi, Bogor City - Sesar Husen Santosa; Agung Prayudha Hidayat; Heryudianto Vibowo (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
Competition for the MSME rice stall business in the city of Bogor is currently very high where business actors are trying to increase consumer loyalty. The problem currently occurring in MSME rice stalls in Bogor City is a lack of knowledge regarding proper handling of food products. This problem means that MSME players only have a limited market share. In this PKM activity, evaluation and implementation of priority improvements are carried out using the Composite Performance Index (CPI). The CPI method uses four alternative options, namely improving service, improving serving facilities, improving food processing methods and improving production layout. The results of determining repair priorities using the CPI method showed that the repair process must be carried out at serving facilities with a value of 106.09. The priority results of this improvement are improvements to the display cases, serving areas and consumer dining tables.